Financial Soundness Analysis of Indonesian Regional Development Banks: A Comparative Case Study Based on the RGEC Framework - Vicka Pramudya Putra; Chairilisa Azzahra (Golden Ratio of Auditing Research, 2026)
Regional Development Banks (RDBs) support regional economic growth through financial intermediation, fund management, and MSME financing. This study examines the financial soundness and governance performance of Bank BJB and Bank Jatim using the RGEC framework during 2021–2025. Using a descriptive quantitative approach, Risk Profile is measured by NPL and LDR, Earnings by ROA and NIM, Capital by CAR, and governance by GCG self-assessment ratings. The findings show that both banks maintained generally sound conditions but had different strengths. Bank BJB performed better in credit quality and governance, while Bank Jatim showed stronger profitability and capital adequacy. Overall, the RGEC framework effectively captures differences in bank soundness across risk, governance, earnings, and capital dimensions. The study highlights the need for RDBs to strengthen risk management, governance, profitability, and capital resilience to support sustainable banking performance.